(untitled) (Journal of Environmental Bioremediation and Toxicology, 2023)
Corrigendum To Hussein Et Al. 2022“Beyond Culturing Approach For Accessing Hydrocarbon-Degrading Microbes In Petroleum Hydrocarbon Polluted Soils: A Perspective” Journal of Environmental Bioremediation and Toxicology, 5(2), 25-35. Https://doi.org/10.54987/Jebat.V512.763,” The second affiliation should be corrected as follows: 2Department of Microbiology, Faculty of Life Sciences, Ahmadu Bello University, 810107, Zaria, Kaduna State, Nigeria.